Structural response analysis of road pavement solar collector (RPSC) with serpentine heat pipes under validated temperature field. (25th January 2021) - Zhou, Bochao; Pei, Jianzhong; Richard Hughes, Ben; SNM Nasir, Diana; Vital, Becky; Pantua, Conrad Allan Jay; Calautit, John; Zhang, Jiupeng
Highlights: The structural response under three different loading conditions was analyzed. Bottom tensile stress, surface deformation, and equivalent stress were used as indexes. The introduction of serpentine heat pipes significantly affects structural response. The structural performance of the area around the heat pipes bend in RPSC is weakest. Abstract: Road Pavement Solar Collector (RPSC) is one of the inevitable products of the diversified development of pavement, which can reduce the temperature of the road surface to mitigate the urban heat island (UHI) effect. The arrangement of the heat pipes in RPSC mainly includes the straight arrangement and the serpentine arrangement. In this study, in order to study the influence of the serpentine heat pipes on the structural response of pavement, the 3D Computational Fluid Dynamics (CFD) - finite element model (FEM) is established and verified. The structural response of conventional pavement and RPSC under three different loading conditions is analysed and compared using ANSYS static structural module. The structural response is analysed from the three indexes of the bottom tensile stress, surface deformation, and equivalent stress. The results show the introduction of heat pipes has a significant effect on the mechanical response, thermal response, and coupling response, and the weakest part of the overall pavement structure is the surrounding of the heat pipe specifically at the bending zone. This study can be a reference for future work to attract the attention of balance the efficiency of heat collection and the structural response for RPSC.